PERBANDINGAN UJI AKTIVITAS ANTIDIABETES EKSTRAK DAUN LIDAH BUAYA DAN LIDAH MERTUA PADA MENCIT PUTIH JANTAN - Erly Sitompul; Supartiningsih Supartiningsih; Rifka Gloria (Jurnal Farmanesia, 2018)
Diabetes mellitus (DM) is a disease whose prevalence is increasing from year to year. This increase was accompanied by an increase in the cost of treatment and the number of complications. The use of traditional medicine is an alternative for the community to control blood sugar levels (KGD). Considering that synthetic drugs have various side effects, one of the medicinal plants used as traditional medicine is aloe vera leaf and mother-in-law's tongue leaf which contain flavonoid compounds, alkaloids, tannins, saponins, and steroids/triterpenoids. The purpose of this study was to determine the antidiabetic activity of aloe vera leaf extract and mother-in-law's tongue and to compare the activities of the two. The results of the analysis of the glucose tolerance ANOVA test showed a significant difference in the percentage reduction at 60, 90, and 120 minutes for all treatment preparations. The alloxan induction test showed a significant difference in the percentage decrease from days 3, 5, 7, 9, 11, 13, and 15. Based on these results, it can be concluded that Aloe Vera Leaf Ethanol Extract (EEDLB) and LidahMertua Leaf Ethanol Extract (EEDLM) with each dose of 150 and 200 mg/kg BW and the combination of the two gave antidiabetic activity against mice as well as differences in effectiveness between samples of aloe vera leaf and LidahMertua leaf as well as a single dose with a combination.